Omega-3 Polyunsaturated Fatty Acids Alleviate Traumatic Brain Injury by Regulating the Glymphatic Pathway in Mice - Zhang, Erwei; Wan, Xiangdong; Yang, Lijun; Wang, Dong; Chen, Zeshang; Chen, Yan; Liu, Minghao; Zhang, Gengshen; Wu, Jianliang; Han, Haie; Fan, Zhenzeng (Frontiers in Neurology, 2020)
Background: The glymphatic pathway has been shown to be impaired in traumatic brain injury (TBI). Omega-3 polysaturated fatty acids (Omega-3, PUFAs) are involved in the clearance of amyloid-ß through the glymphatic system and this effect is Aquaporin-4 (AQP4) dependent. We hypothesize that Omega-3 PUFAs can alleviate neurological impairment in TBI by protecting the glymphatic pathway. Methods: We pretreated mice with Omega-3 PUFAs rich fish oil and introduced TBI in the mice. Neurological functions were assessed through the modified neurological severity score (mNSS) system and Rota-rod test. Aß42 levels and radioisotope clearance were examined to determine the function of glymphatic system. AQP4 protein and mRNA expressions and its polarity were examined in fish oil treated TBI mice or control mice. Finally, the integrity of blood-brain barrier was determined by Evans blue extravasation and measurement of tight junction proteins (ZO-1 and Occludin) levels. Results: TBI surgery induced significant neurological functional impairment, Omega-3 PUFAs attenuated TBI-induced neurological impairment, as evidenced by reduced mNSS, improved performance in the Rota-rod test. Furthermore, Omega-3 PUFAs improved glymphatic clearance after induction of TBI in mice, reduced Aß42 accumulation, partially restored the clearance of both 3H-mannitol and 14C-Inulin. Omega-3 PUFAs also suppressed AQP4 expression and partially prevented loss of AQP4 polarity in mice undergoing TBI. Finally, Omega-3 PUFAs protected mice from TBI induced blood-brain barrier disruption. Conclusion: Omaga-3 PUFAs attenuate neurological function by partially restoring the AQP4 dependent glymphatic system in mice with TBI.